MENELUSURI KONSEP GENDER DALAM AL-QUR’AN - Nurbaeti Nurbaeti (LPPM IAIN Parepare, 2018)
This paper examines gender in an Islamic perspective. In Islam there are several controversy issues related to gender relations, including the origin of the creation of women, the concept of inheritance, witnessing, polygamy, reproductive rights, the rights of female divorces, and the public role of women. This fact will be very interesting if it is related to the Koran as the main source of Islamic teachings. Al-Quran does not deny the existence of differences (distinction) between men and women but these differences are not differences (discrimination) that benefit one party and harm the other party. By basing on the main sources of Islamic teachings, namely the Koran and Hadith, it was found some disclosures of the meaning of words related to gender such as al-rajul wa al-nisa, al-zakar wa al-untsa and al-mar'u and al-mar'ah. Various explanations in detail and globally regarding the position of men and women in accordance with their respective nature. They are created in pairs, like two sides of a coin that cannot be separated in an effort to expand their duties as khalifatullah fil ardi.